Maintenance of photosynthesis and the antioxidant defence systems have key roles for survival of Halopeplis perfoliata (Amaranthaceae) in a saline environment. (23rd August 2019) - Rasool, S. G.; Gulzar, S.; Hameed, A.; Edwards, G. E.; Khan, M. A.; Gul, B.
Abstract: Coastal salt marsh plants employ various combinations of morphological and physiological adaptations to survive under saline conditions. Little information is available on salinity tolerance mechanisms of Halopeplis perfoliata, a C3 stem succulent halophyte. We investigated the growth, photosynthesis and antioxidant defence mechanisms of H. perfoliata under saline conditions (0, 150, 300 and 600 mM NaCl) in an open greenhouse. Optimal shoot succulence, projected shoot area and relative growth rate were obtained in the low (150 mm NaCl) salinity treatment, while growth was inhibited at the highest salinity (600 mm NaCl). The CO2 compensation point and carbon isotope composition of biomass confirmed C3 photosynthesis. Increases in salinity did not affect the photosynthetic pigment content or maximum quantum efficiency of PSII of H. perfoliata . Assimilation of CO2 ( A ) also remained unaffected by salinity. A modest effect on some gas exchange and photochemistry parameters was observed at 600 mm NaCl. With increasing salinity, there was a continual increase in respiration, suggesting utilisation of energy to cope with saline conditions. Under 300 and 600 mm NaCl, there was an increase in H2 O2 and MDA with a concomitant rise in AsA, GR content and CAT activity. Hence, H.   perfoliata appears to be an obligate halophyte that can grow up to seawater salinities by modulating photosynthetic gas exchange, photochemistry and the antioxidant defence systems. Abstract : Halopeplis perfoliata has high tolerance to salinity (up to the NaCl of seawater), which may result, at least partially, from the maintenance of photosynthesis and antioxidant defence systems.